Modular Ontologies Concepts, Theories and Techniques for Knowledge Modularization - Stuckenschmidt, Heiner; Parent, Christine; Spaccapietra, Stefano (Theoretical Computer Science and General Issues,, 2009)
This book constitutes a collection of research achievements mature enough to provide a firm and reliable basis on modular ontologies. It gives the reader a detailed analysis of the state of the art of the research area and discusses the recent concepts, theories and techniques for knowledge modularization. The 13 papers presented in this book were all carefully reviewed before publication. They have been organized in three parts: Part I gives a general introduction to the idea and issues characterizing modularization and offers an in-depth analysis of properties, criteria and knowledge import techniques for modularization. Part II describes four major research proposals for creating modules from an existing ontology either by partitioning an ontology into a collection of modules or by extracting one or more modules from the ontology. Part III reports on collaborative approaches where modules that pre-exist are linked together through mappings to form a virtual large ontology.